2016
DOI: 10.1371/journal.pone.0165446
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Transplanting Various Concentrations of a Composite of Human Umbilical Cord Blood-Derived Mesenchymal Stem Cells and Hyaluronic Acid Hydrogel on Articular Cartilage Repair in a Rabbit Model

Abstract: BackgroundMesenchymal stem cells (MSCs) are known to have therapeutic potential for cartilage repair. However, the optimal concentration of MSCs for cartilage repair remains unclear. Therefore, we aimed to explore the feasibility of cartilage repair by human umbilical cord blood-derived MSCs (hUCB-MSCs) and to determine the optimal concentrations of the MSCs in a rabbit model.MethodsOsteochondral defects were created in the trochlear groove of femur in 55 rabbits. Four experimental groups (11 rabbits/group) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 42 publications
2
18
0
Order By: Relevance
“…However, these findings were not consistent with other studies. In a dose escalation study reported by Park et al, efficacy of human umbilical cord blood-derived MSCs for cartilage repair was higher in lower MSC doses (0.1, 0.5, and 1 × 10 7 cells) than those in higher dose (1.5 × 10 7 cells) [38]. It might be proper to consider several factors such as the source of the cells, their characteristic, and route and delivery vehicle for cell Patients with osteoarthritis and other degenerative musculoskeletal diseases in knees got additional intra-articular injection, and those who had presented with cerebral palsy, autism, stroke, Parkinson's disease, and dementia also got additional spinal injection of SVF on the day of first infusion.…”
Section: Discussionmentioning
confidence: 93%
“…However, these findings were not consistent with other studies. In a dose escalation study reported by Park et al, efficacy of human umbilical cord blood-derived MSCs for cartilage repair was higher in lower MSC doses (0.1, 0.5, and 1 × 10 7 cells) than those in higher dose (1.5 × 10 7 cells) [38]. It might be proper to consider several factors such as the source of the cells, their characteristic, and route and delivery vehicle for cell Patients with osteoarthritis and other degenerative musculoskeletal diseases in knees got additional intra-articular injection, and those who had presented with cerebral palsy, autism, stroke, Parkinson's disease, and dementia also got additional spinal injection of SVF on the day of first infusion.…”
Section: Discussionmentioning
confidence: 93%
“…To help solve this, local injection of hydrogel-embedded MSCs may be a strategy combining long-lasting secretome production with increased control over the cell fate. This has already been explored in several fields, for instance bone or cartilage regeneration [25] , [26] , but also acute neurodegeneration as in traumatic brain injury [27] , but there is no information in the field of chronic neurodegenerative disorders such as Parkinson’s disease. We have developed biocompatible hydrogels that may be valuable in this area.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported that MSCs with scaffold can repair osteochondral defects in animal models [ 40 43 ]. We have already experienced successful restoration of osteochondral defects with no immunologic problem after transplantation of human UCB-MSCs in an animal model which was a xenograft model [ 22 26 ]. Also, we had seen the safety and efficacy of UCB-MSCs for the restoration of articular cartilage defect in seven osteoarthritic patients in phase 1/2 clinical trial performed at our institution [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that transplanting of UCB-MSCs and hyaluronic acid hydrogel composite resulted in favorable cartilage repair in animal models [ 22 26 ]. Moreover, recently, we demonstrated that transplantation a composite of allogeneic UCB-MSCs and HA hydrogel was safe and effective modality for cartilage repair in osteoarthritic knees, which was followed up for more than 7 years without any significant adverse events [ 27 ].…”
Section: Introductionmentioning
confidence: 99%